Clinical utility of the risperidone formulations in the management of schizophrenia - Madaan, Vishal (Dove Medical Press, 2011)
Risperidone is one of the early second-generation antipsychotics that came into the limelight in the early 1990s. Both the oral and long-acting injectable formulations have been subject to numerous studies to assess their safety, efficacy, and tolerability. Risperidone is currently one of the most widely prescribed antipsychotic medications, used for both acute and long-term maintenance in schizophrenia. Risperidone has better efficacy in the treatment of psychotic symptoms than placebo and possibly many first-generation antipsychotics. Risperidone fares better than placebo and first-generation antipsychotics in the treatment of negative symptoms. Risperidone’s long acting injectable preparation has been well tolerated and is often useful in patients with medication nonadherence. Risperidone has a higher risk of hyperprolactinemia comparable to first-generation antipsychotics (FGAs) but fares better than many second-generation antipsychotics with regards to metabolic side effects. In this article, we briefly review the recent literature exploring the role of risperidone formulations in schizophrenia, discuss clinical usage, and highlight the controversies and challenges associated with its use.